Advertisement Remove all ads

Solve the Following Quadratic Equation by Using Formula Method : 2x2 - 3x = 2 - Algebra

Sum

Solve the following quadratic equation by using formula method :

2x2 - 3x = 2

Advertisement Remove all ads

Solution

Given quadratic equation

2x2 - 3x = 2

2x2 - 3x - 2 = 0

a = 2, b = -3, c = -2

By Formula method,

`x = (-b +-sqrt(b^2 - 4ac))/(2a)`

`= (3+-sqrt(9-4(2)(-2)))/(2(2))`

`= (3+-sqrt(9+16))/4`

`= (3 +-5)/4`

`x = (3+5)/4   or x = (3-5)/4`

∴ x = `2, (-1)/2`

  Is there an error in this question or solution?
Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×